SUPPLIER-INDUCED DEMAND AND HEALTHCARE IN LOKOJA - Rabi’u Isah Moh’d; Mathew Ekundayo Rotimi (International Studies Journal)
This study investigates the existence of supplier-induced demand for healthcare in Nigeria’s healthcare system where private healthcare provision and fee-for-service mode of payment are order of the day. Using primary data sourced from 379 respondents, the study estimates Linear Probability Model (LPM), to establish the relationship between supplier inducement and demand for healthcare. Findings from the study revealed that there is no statistically significant evidence to suggest the existence of supplier-induced demand for healthcare among the privately-owned hospitals in Lokoja. However, the study finds education and enrolment in health insurance to be negatively and statistically significantly correlated with supplier inducement. Having high education and enrolment in the health insurance scheme curtail the probability of receiving dubious care. Therefore, this research recommends, among others, that the government should make high education more accessible to the citizens by way of subsidizing tuition fees charged by universities, and providing soft education loans to eligible citizens. It recommends further that governments at all levels should provide health insurance for all.